2005
DOI: 10.3133/sir20055131
|View full text |Cite
|
Sign up to set email alerts
|

Sediment studies in the Assabet River, central Massachusetts, 2003

Abstract: From its headwaters in Westborough, Massachusetts, to its confluence with the Sudbury River, the 53-kilometer-long Assabet River passes through a series of small towns and mixed land-use areas. Along the way, wastewater-treatment plants release nutrient-rich effluents that contribute to the eutrophic state of this waterway. This condition is most obvious where the river is impounded by a series of dams that have sequestered large amounts of sediment and support rooted and floating macrophytes and epiphytic alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…This dissolved phosphorus and any phosphorus associated with ferric oxyhydroxides would serve as a dissolved-phosphorus reservoir that could be released into the water column if anoxic conditions develop and could break down the oxidized microzone at the sediment-water interface. (Although the existence of iron-rich, oxidized microzones in the Assabet River impoundments was not investigated here, Zimmerman and Sorenson (2005) found that surficial-sediment samples in the impoundments generally had iron concentrations higher than 1 percent by mass. In all likelihood, a substantial portion of this iron would have been in the oxidized form.)…”
Section: Results Of Sampling In Free-flowing and Impounded Reachesmentioning
confidence: 80%
See 2 more Smart Citations
“…This dissolved phosphorus and any phosphorus associated with ferric oxyhydroxides would serve as a dissolved-phosphorus reservoir that could be released into the water column if anoxic conditions develop and could break down the oxidized microzone at the sediment-water interface. (Although the existence of iron-rich, oxidized microzones in the Assabet River impoundments was not investigated here, Zimmerman and Sorenson (2005) found that surficial-sediment samples in the impoundments generally had iron concentrations higher than 1 percent by mass. In all likelihood, a substantial portion of this iron would have been in the oxidized form.)…”
Section: Results Of Sampling In Free-flowing and Impounded Reachesmentioning
confidence: 80%
“…Parker and others (2004) found that the high proportion of tolerant generalist fish species among the fish communities in the Assabet River Basin indicated a degraded aquatic ecosystem. Zimmerman and Sorenson (2005) reported the results of sediment sampling in six Assabet impoundments and of their investigation of phosphorus dynamics in the Hudson impoundment. Sediment cores from a predetermined number of randomly selected sites in each impoundment were analyzed for bulk chemical properties, including TP, trace metals, volatile organic compounds, organochlorine pesticides, polycyclic aromatic compounds, polychlorinated biphenyls, and extractable petroleum hydrocarbons.…”
Section: Previous Investigations In the Assabet River Basinmentioning
confidence: 99%
See 1 more Smart Citation
“…The SuAsCo watershed encompasses many impoundments, and anaerobic conditions in deep water provide a conducive environment for phosphorus to unbind. This dissolved phosphorus is then taken up by aquatic plants [57], and these floating plants further reduce dissolved oxygen and create eutrophic conditions in the water. Changes in phosphorus over the LTM scenarios are more strongly related to increasing phosphorus outputs from urban rather than agricultural sources (Table 7).…”
Section: Assessment Of Changes In Land Use On Sediments (Tss) and Nut...mentioning
confidence: 99%
“…In addition, the rivers in the SuAsCo watershed were designated for five "outstandingly remarkable values": history, scenery, recreation, ecology, and place in American literature. However, because of impairment caused by sediments and nutrients, the Assabet, Sudbury, and Concord rivers no longer met the criteria for Class B (fishable and swimmable) in 2001 [57]. Now, these rivers are on the State's List of Impaired Waters (303d) under the Clean Water Act [58].…”
Section: Introductionmentioning
confidence: 99%